Gastrointestinal Mantle Cell Lymphoma: incidental finding on routine CT scan following pneumothorax. - Sherpa, Mingma Thsering; Rondelli, Damiano; Shrestha, Raksha (Journal of Advances in Internal Medicine, 2013)
Gastric mantle cell lymphoma is a rare form of gastrointestinal tumor and represents 2.5–7% of all non-Hodgkin’s lymphomas. A 69-year-old maleadmitted with spontaneous pneumothorax was found to have a gastric masson CT scan. Results of histopathological,immunohistochemical and genetic analysis were consistent with mantle cell lymphoma(MCL).Patient responded well to intensive chemotherapy and subsequent allogeneic hematopoietic stem cell transplant and remains in complete remission.We would like to emphasize that a gastric mass, as in this case can occur as a rare presentation of MCL involving the gastrointestinal tract without any other overt signs and symptoms. Journal of Advances in Internal Medicine 2013;02(01):24-26 DOI: http://dx.doi.org/10.3126/jaim.v2i1.7635